Molecular donor-acceptor dyads for efficient single-material organic solar cells - Lucas, Sebastian; Kammerer, Jochen; Pfannmöller, Martin; Schröder, Rasmus R.; He, Yakun; Li, Ning; Brabec, Christoph J.; Leydecker, Tim; Samorì, Paolo; Marszalek, Tomasz; Pisula, Wojchiech; Mena-Osteritz, Elena; et al. (Solar RRL, 2021)
Single-material organic solar cells (SMOSCs) promise several advantages with respect to prospective applications in printed large-area solar foils. Only one photoactive material has to be processed and the impressive thermal and photochemical long-term stability of the devices is achieved. Herein, a novel structural design of oligomeric donor-acceptor (D-A) dyads 1-3 is established, in which an oligothiophene donor and fullerene acceptor are covalently linked by a flexible spacer of variable length. Favorable optoelectronic, charge transport, and self-organization properties of the D-A dyads are the basis for reaching power conversion efficiencies up to 4.26% in SMOSCs. The dependence of photovoltaic and charge transport parameters in these ambipolar semiconductors on the specific molecular structure is investigated before and after post-treatment by solvent vapor annealing. The inner nanomorphology of the photoactive films of the dyads is analyzed with transmission electron microscopy (TEM) and grazing-incidence wide-angle X-ray scattering (GIWAXS). Combined theoretical calculations result in a lamellar supramolecular order of the dyads with a D-A phase separation smaller than 2 nm. The molecular design and the precise distance between donor and acceptor moieties ensure the fundamental physical processes operative in organic solar cells and provide stabilization of D-A interfaces.
Online veröffentlicht: 7. November 2020
Gesehen am 22.03.2024
Dedicated to Professor Franz Effenberger on the occasion of his 90th birthday